Legal Protection for Children as Perpetrators of Sexual Violence - Arifulloh, Achmad (KnE Social Sciences, 2025)
Children as perpetrators of sexual violence crimes presents a complex dilemma in the Indonesian criminal justice system. On the one hand, there is a need to provide justice for victims and enforce the law, but on the other hand, the state is obliged to provide special protection for children involved in the law based on the Child Criminal Justice System Law (UU SPPA). Children in conflict with the law, whether due to coercion, ignorance, or environmental factors, require a different approach from adult perpetrators. This research is normative legal research using a statutory and conceptual approach. Data collection was carried out through a literature study of primary legal materials such as laws and regulations, secondary legal materials in the form of books and scientific journals, and tertiary legal materials. The results of the study show that the legal system in Indonesia has adopted the principle of the best interest of the child through diversion and restorative justice mechanisms. Legal protection is provided at every stage of the trial, from investigation to post-decision guidance, with a focus on rehabilitation rather than retribution. Child perpetrators can be subject to action, not criminal sanctions in prison, which are adjusted to their age and level of guilt. However, its implementation still faces challenges such as social stigma, limited capacity of foster institutions, and harmonization between the rights of children as perpetrators and the rights of victims.